2015
DOI: 10.1002/tie.21751
|View full text |Cite
|
Sign up to set email alerts
|

Colliding Employer-Employee Perspectives of Employee Turnover: Evidence from a Born-Global Industry

Abstract: Set in the context of internationalization of the global division of labor, this article provides a deeper exploration of qualitative themes of confl icting accounts of employees' reasons to quit and managerialstrategies to prevent employee turnover in six business process outsourcing fi rms operating in India. Such differences in cognition and action between the two constituencies suggest that the decisionto quit is not a linear and rational process as highlighted in most extant models of employee turnover. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 83 publications
(110 reference statements)
1
6
0
1
Order By: Relevance
“…Furthermore, we have found that perception of turnover risk has a mediating effect between carbon emission reduction policy and turnover intention. Thus, it can be concluded that employees' perceptions of turnover risk can harm employee satisfaction and well-being and enhance job burnout, these finding were consistent with the previous studies [43][44][45][73][74][75][76]. Moreover, we found that green transformational leadership has an essential inhibiting effect on the perception of turnover risk and turnover intention among employees in energy-intensive corporations.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we have found that perception of turnover risk has a mediating effect between carbon emission reduction policy and turnover intention. Thus, it can be concluded that employees' perceptions of turnover risk can harm employee satisfaction and well-being and enhance job burnout, these finding were consistent with the previous studies [43][44][45][73][74][75][76]. Moreover, we found that green transformational leadership has an essential inhibiting effect on the perception of turnover risk and turnover intention among employees in energy-intensive corporations.…”
Section: Discussionsupporting
confidence: 91%
“…The contents of the transactional psychological contract covered availability of basic infrastructure to complete work tasks, regular training, and a fair and transparent reward system. Further, in harmony with the literature, while job security was an important employer obligation (Eisner, ), career security was identified as an crucial expectation (Lancaster & Stillman, ; Pereira, Malik, & Sharma, ). Relational expectations included aspects related to job content such as freedom to act independently and availability of learning and development opportunities.…”
Section: Discussionmentioning
confidence: 53%
“…The turnover time is about two years. Therefore, the company wants to retain the employees and gave a high weight to this criterion (Pereira et al, 2015). The weight of the sub-criteria must be multiplied by the weight of flexibility (e.g.…”
Section: Criteriamentioning
confidence: 99%